2019
DOI: 10.4103/1735-3327.261155
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study on the release of nickel, chromium, and zinc in saliva and serum from patients treated with fixed orthodontic appliances

Abstract: Background: Fixed orthodontic appliances can release metal ions such as nickel, chromium, and zinc into saliva and blood, which can cause contact dermatitis, hypersensitivity, and cytotoxicity. This study was undertaken to assess the release of nickel, chromium, and zinc in saliva and serum of patients undergoing fixed orthodontic treatment. Materials and Methods: This in vivo study was conducted on 80 participants with an age range of 15–40 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Amongst them, stainless steel, nickel-titanium, β-titanium and cobalt-chromium alloys are the most commonly used orthodontic materials. Previous studies have shown that orthodontic appliances made out of the previously mentioned materials release metal ions over time [39]. The amount of released metal ions is largely dependent on the type of alloy, surrounding environment and the exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst them, stainless steel, nickel-titanium, β-titanium and cobalt-chromium alloys are the most commonly used orthodontic materials. Previous studies have shown that orthodontic appliances made out of the previously mentioned materials release metal ions over time [39]. The amount of released metal ions is largely dependent on the type of alloy, surrounding environment and the exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…Bhasin et al [ 10 ] showed that during the period of fixed orthodontic treatment, nickel and chromium levels elevated the gingival crevicular fluid (GCF) and showed increasing signs of gingival inflammation as well as oral mucosa cells [ 11 ]. Over the treatment period, serum levels can increase, although they do not reach toxic levels, as per the report of Quadras et al [ 12 ]. Fitjer et al [ 13 ] were able to prove that the wires inside of polymerised acrylic resin of removable appliances corrode, leading to discolorations of the resin and loss of sheen on the surface of the metal.…”
Section: Introductionmentioning
confidence: 56%
“…In fact, nickel has a high allergen potential, which can cause discoloration of adjacent soft tissues, pain or allergic reactions (Quadras et al, 2019). Therefore, all selected articles related the presence of this substance to the appearance of allergic reactions in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%